DTAACS: distributed task allocation for adaptive computational system based on organization knowledge - Valenzuela, Jorge L. (Kansas State University, 2014)
The Organization-Based Multi-Agent Systems (OMAS) paradigm is an approach to address the challenges posed by complex systems. The complexity of these systems, the changing environment where the systems are deployed, and satisfying higher user expectations are some of current requirements when designing OMAS. For the agents in an OMAS to pursue the achievement of a common goal or task, a certain level of coordination and collaboration occurs among them. An objective in this coordination is to make the decision of who does what. Several solutions have been proposed to answer this task allocation question. The majority of the solutions proposed fall in the categories of marked-based approaches, reactive systems, or game theory approaches. A common fact among these solutions is the system information sharing among agents, which is used only to keep the participant agent informed about other agents activities and mission status. To further exploit and take advantage of this system information shared among agents, a framework is proposed to use this information to answer the question who does what, and reduce the communication among agents. DTAACS-OK is a distributed knowledge-based framework that addresses the Single Agent Task Allocation Problem (SAT-AP) and the Multiple Agent Task Allocation Problem (MAT-AP) in cooperative OMAS. The allocation of tasks is based on an identical organization knowledge posses by all agents in the organization. DTAACS-OK di ers with current solutions in that (a) it is not a marked-based approach where task are auctioned among agents, or (b) it is not based on agents behaviour, where the action or lack of action of an agent cause the reaction of other agents in the organization.
Keywords: Multi-Agent systems; Distributed task allocation; Software engineering; Computer sciences; Computer Science (0984)